No effects of a short-term gluten-free diet on performance in nonceliac athletes - Lis, D.; Stellingwerff, T.; Kitic, C. M.; Ahuja, K. D. K.; Fell, J. (Medicine & Science in Sports & Exercise, 2015)
Purpose: Implementation of gluten-free diets among nonceliac athletes has rapidly increased in recent years because of perceived ergogenic and health benefits. The aim of this study was to investigate the effects of a gluten-free diet (GFD) on exercise performance, gastrointestinal (GI) symptoms, perceived well-being, intestinal injury, and inflammatory responses in nonceliac athletes.